Epilepsy, Comorbidities and Treatments - Guekht, Alla (Current Pharmaceutical Design, 2017)
Background: An increasing amount of evidence suggests an association between epilepsy and multiple somatic and psychiatric conditions, which is more significant than in the general population. Furthermore, a bidirectional association has been established between epilepsy and several conditions, notably depression and suicide, cerebrovascular disease, stroke, dementia and migraine, which is best explained by the presence of common underlying mechanisms and risk factors. Gaining knowledge about these common mechanisms can provide insight into new therapeutic targets, screening and preventive measures. Methods: This review discusses several of the more significant somatic and psychiatric comorbidities of epilepsy, the mechanisms and direction of their association, as well as the implications of these comorbidities for treatment. Results: Somatic and psychiatric comorbidity in epilepsy have been investigated in several population-based studies using medical records databases and different survey methods. All show a significantly higher prevalence for a number of medical conditions in people with epilepsy (PWE) compared to the general population. Conclusion: The coexistence of different medical conditions with epilepsy carries important implications for the assessment of the burden of the disease and the outcome and management of these patients, as they often require long-term antiepileptic drug intake.
Keywords: Comorbidities